The five practices in practice : successfully orchestrating mathematical discourse in your middle school classroom - Smith, Margaret Schwan (Corwin, 2019)
"Helping other people understand and love the math you understood and loved - perhaps that sounded like a good way to spend a few decades. Or perhaps you loved kids. Perhaps even at a young age you were an effective caregiver, but you knew how to care for more than just another person's tangible needs. You listened, and you made people feel listened to. You had an eye for a person's value and power, especially people who felt like they were powerless and had very little value to offer anybody else. You understood where people were in their lives and you understood how the right kind of question or observation could propel them to where they were going to be. Spending a few decades helping people feel heard, helping them unbury and use their tremendous capacity - perhaps you thought there were worse ways to spend what you thought would only be the hours between 7AM and 4PM every day"--